Acessibilidade em museus de arte: questões para a elaboração de audioguias - Marchezi, Fabiana (2012)
This work is the result of a study about audioguides used in art museums as a resource to accessibility for the blind and visually impaired individuals. We started from the concept of disability and accessibility and two sets were considered for the analysis of the audioguides. The first set refers to the analysis of verbal discourses conveyed in the audioguides, in special description, the textual mode present in all audioguides searched. The second set refers to the sound elements present in the audioguides, wich for purposes of this paper were understood as soundtracks. The audioguides used in this study were collected from the Museum of Modern Art of São Paulo (MAM), The Museum of Modern Art, New York (MoMA), The Metropolitan Museum of Art (The Met) and Pinacoteca do Estado de São Paulo.